INCLUSIVE-PLURALISTIC ISLAMIC RELIGIOUS EDUCATION MODEL AS AN ALTERNATIVE TO INVESTING THE VALUES OF RELIGIOUS MODERATION - Zeni Murtafiati Mizani (Muslim Heritage, 2022)
AbstractThis research departs from Islamic Religious Education which is felt to be incomplete in teaching the values of diversity to students so that it can cause students to live in intolerant nuances. This research seeks to provide an overview of an inclusive and pluralist Model of Islamic religious education as an alternative to realizing religious moderation. The research approach used in this study is a Systematic Literature Review with data collection carried out by analyzing or reviewing relevant research writings and articles. The data analysis technique used by researchers is a descriptive synthesis analysis technique (narrative). The result of this study inclusive-pluralistic Islamic religious education is an educational model that is constructed using an understanding and foundation of differences that include sunnatullah, showing the spirit of tolerance, religion, and pluralism, to produce educational outputs that have humanist, democratic, tolerant, pluralist behavior so that the character of students is formed by religious and national values. The pluralist inclusive Islamic religious education model can be seen in terms of the curriculum which includes material that reflects the vision of appreciation and peace towards other religions. These methods allow freedom of thought, and evaluation that is open to all stakeholders, not just students. Then also educators are touched by the discourse of religious thought and the struggle of thought on issues surrounding pluralism, interfaith dialogue, and tolerance. And finally, students are seen as individuals with the potential to have social care and critical thinking skills.  AbstrakPenelitian ini berangkat dari Pendidikan Agama Islam yang dirasa kurang lengkap dalam mengajarkan nilai-nilai kebhinnekaan kepada peserta didik, sehingga dapat menyebabkan peserta didik hidup dalam nuansa intoleran. Penelitian ini bertujuan memberikan gambaran tentang Model pendidikan agama Islam yang inklusif dan pluralis sebagai alternatif mewujudkan moderasi beragama. Pendekatan penelitian yang digunakan dalam penelitian ini adalah Systematic Literature Review dengan pengumpulan data dilakukan dengan menganalisis atau menelaah tulisan dan artikel penelitian yang relevan. Teknik analisis data yang digunakan peneliti adalah teknik analisis deskriptif sintesis (naratif). Hasil penelitian ini pendidikan agama Islam inklusif-pluralis merupakan model pendidikan yang dibangun dengan menggunakan pemahaman dan landasan perbedaan yang meliputi sunnatullah, menunjukkan semangat toleransi, beragama dan pluralisme, sehingga menghasilkan output pendidikan yang humanis, demokratis., toleran, pluralis sehingga terbentuk karakter peserta didik yang sesuai dengan nilai-nilai agama dan kebangsaan. Model pendidikan agama Islam inklusif pluralis dapat dilihat dari segi kurikulum yang memuat materi yang mencerminkan visi penghargaan dan perdamaian terhadap agama lain, metode yang memungkinkan kebebasan berpikir, evaluasi yang terbuka untuk semua pemangku kepentingan, tidak hanya peserta didik. Kemudian para pendidik juga tersentuh wacana pemikiran keagamaan dan pergumulan pemikiran tentang isu-isu seputar pluralisme, dialog antaragama, dan toleransi. Dan terakhir, siswa dipandang sebagai individu yang berpotensi memiliki kepedulian sosial dan kemampuan berpikir kritis.